(untitled) (Revista Educação, Artes e Inclusão, 2021)
Education is the foundation of the growth and development of any society. In Angola it is no exception even though the country has achieved independence in 1975. The situation of corruption in the Angolan primary and secondary school is worrisome because it reduces the quality of teaching and causes disbelief of the school. Where there is corruption professionalism does not reach the desired levels. The research aims to (i) identify the factors that contribute to corruption; (ii) discussing public policies to combat corruption; (iii) propose ways to improve the civic and moral responsibility of schools in order to combat "schemes" of corruption. Using the bibliographic method, it was concluded that it is necessary for the Angolan Government to adopt educational policies that help improve the quality of education. It is important that the Government bet on the training of teachers with quality, improving the infrastructural conditions of schools that will decrease the demand for enrollment vacancies. Parents should take responsibility for the school by participating in the school process and by supporting teachers and students. Schools should receive full support from the Government so that education does not form functional illiterates.